2020
DOI: 10.1088/1361-6498/ab749e
|View full text |Cite
|
Sign up to set email alerts
|

Results of the first national indoor radon survey performed in Serbia

Abstract: The first step in every systematic approach to investigating population exposure to radon on a national level is to perform a comprehensive indoor radon survey. Based on general knowledge of the radon levels in Serbia and corresponding doses, the results obtained from a national indoor radon survey would allow policymakers to decide whether it is necessary to establish a national radon programme. For this reason, Serbia initiated work on a national radon action plan (RAP) in 2014 when it was decided to carry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In Serbia, the national reference level for indoor radon concentration for new buildings is 200 Bq/m 3 , for the existing buildings is 400 Bq/m 3 , while 1000 Bq/m 3 is the upper level recommended for workplaces. A new national radon survey has shown that in 3% of all measurements the level of 400 Bq/m 3 has been exceeded [27].…”
Section: Indoor Radon Levelmentioning
confidence: 99%
“…In Serbia, the national reference level for indoor radon concentration for new buildings is 200 Bq/m 3 , for the existing buildings is 400 Bq/m 3 , while 1000 Bq/m 3 is the upper level recommended for workplaces. A new national radon survey has shown that in 3% of all measurements the level of 400 Bq/m 3 has been exceeded [27].…”
Section: Indoor Radon Levelmentioning
confidence: 99%
“…So, in the countries of the European Union, the concept of "geogenic radon potential" is key in assessing the potential radon hazard of territories [6][7][8][9]. At the same time, in different countries, the concept is based on various factors: in Serbia -the content of natural radionuclide in the soil [10], in Norway -the correlation between indoor radon and geology [11], in Switzerland -the dose rate of gamma radiation, geology, lines faults, permeability of the upper soil layer [12].…”
Section: Introductionmentioning
confidence: 99%